2021
DOI: 10.1186/s12985-021-01548-6
|View full text |Cite
|
Sign up to set email alerts
|

STING and cGAS gene expressions were downregulated among HIV-1-infected persons after antiretroviral therapy

Abstract: Background The HIV-1 epidemic is still considered a global public health problem, but great advances have been made in fighting it by antiretroviral therapy (ART). ART has a considerable impact on viral replication and host immunity. The production of type I interferon (IFN) is key to the innate immune response to viral infections. The STING and cGAS proteins have proven roles in the antiviral cascade. The present study aimed to evaluate the impact of ART on innate immunity, which was represent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…To survive in the host cells such as macrophages, HIV has evolved the strategies to avoid and/or suppress the intracellular innate immunity. Lima et al showed that STING and cGAS gene expressions were downregulated among HIV‐infected persons after antiretroviral therapy 55 . In addition, a very recent paper demonstrated that through its capsid the pandemic HIV M strain can inhibit cGAS and TRIM5 activation, which results in silent viral replication in myeloid cells 56 .…”
Section: Discussionmentioning
confidence: 99%
“…To survive in the host cells such as macrophages, HIV has evolved the strategies to avoid and/or suppress the intracellular innate immunity. Lima et al showed that STING and cGAS gene expressions were downregulated among HIV‐infected persons after antiretroviral therapy 55 . In addition, a very recent paper demonstrated that through its capsid the pandemic HIV M strain can inhibit cGAS and TRIM5 activation, which results in silent viral replication in myeloid cells 56 .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of symptoms related to long COVID in the investigated group is described in Table 1. These patients were treated at the outpatient clinic for long COVID at the State University of Pará 25 .…”
Section: Participant Characteristics and Sample Collectionmentioning
confidence: 99%
“…The concentration of the extracted RNA was determined using a BioDrop™ (Bio-Rad, Hercules, California, USA) according to the manufacturer's instructions. The concentrations of all total RNA samples for synthesis of complementary DNA (cDNA) were equal to 50 ng/µL 25 www.nature.com/scientificreports/…”
Section: Rna Extraction and Reverse Transcriptionmentioning
confidence: 99%
See 2 more Smart Citations